T-cell antigen receptor binding sites for the microbial superantigen staphylococcal enterotoxin A. - Pontzer, C H (1992)
We have examined the interaction of the microbial superantigen staphylococcal enterotoxin A (SEA) with peptides corresponding to overlapping regions of the T-cell antigen receptor beta chain variable region V beta 3. SEA is known to stimulate murine T cells bearing certain V beta elements, among them V beta 3. Five peptides were synthesized representing amino acids 1-24, 20-44, 39-60, 57-77, and 74-95 of V beta 3. We demonstrate here that soluble V beta 3-bearing beta chains can bind to a complex of SEA and major histocompatibility complex class II and that the synthetic peptide V beta 3-(57-77) blocked this interaction. The peptide V beta 3-(57-77) also inhibited SEA-induced interferon-gamma production and SEA-induced proliferation of B10.BR spleen cells. Conversely, the peptide corresponding to amino acids 57-77 of V beta 8.2, a V beta element that is not recognized by SEA, decreased staphylococcal enterotoxin C-2-induced proliferation but did not affect SEA-induced proliferation. The peptide inhibition of SEA-induced function was due at least in part to inhibition of V beta 3-bearing T-cell activity, since the percentage of T cells reactive with an anti-V beta 3 monoclonal antibody was significantly reduced by V beta 3-(57-77). These data suggest that the region of V beta 3 encompassing amino acids 57-77 is an area that displays the appropriate sequence and conformation for binding of the SEA molecule and blocking of the resultant interaction with the T-cell antigen receptor.